PEREMPUAN MANDIRI DALAM NOVEL BUMI MANUSIA KARYA PRAMUDYA ANANTA TOER DAN DRAMA MUTTER COURAGE UND IHRE KINDER KARYA BERTOLT BRECHT - Haryati, Isti (Sunan Kalijaga State Islamic University Yogyakarta, 2020)
The purpose of this study to describe and reveal the comparation of the independence of female characters in Pramoedya Ananta Toer’s Bumi Manusia and in Bertolt Brecht’s Mutter Courage und Ihre Kinder. This research is a qualitative descriptive study using the comparative literature method. This research will describe and comprehend the comparison of independent female characters in the Pramudya Ananta Toer’s Bumi Manusia and in Brecht’s Mutter Courage und Ihre Kinder by Bertolt Brecht. The results showed that from the comparison of two independent female character in two literary works, namely novel Bumi Manusia and drama Mutter Courage und Ihre Kinder, it can be concluded that there are many similarities of the two independent female characters despite the difference. Equation (affinity) also showed that the two works were created by different authors are also mutually influence. Drama Mutter Courage und Ihre Kinder by Bertolt Brecht created in 1938 possibly affect Bumi Manusia novel created by Pramoedya Ananta Toer in 1975. Moreover, both authors are communist and they created the two literary works while in exile.